THE USE OF BEELINGUAPP TO ENHANCE STUDENTS’ RECOUNT TEXT READING COMPREHENSION - Karimah, Inayatul (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aimed to measure the effectiveness of Beelinguapp in enhancing students’ reading comprehension of recount text. This study employed quantitative method with pre-experimental research design. A total number of 38 students of grade VIII SMP Islamiyah Ciputat, South Tangerang, participated as the sample of this research. In collecting the data, both pre-test and post-test of recount text reading comprehension were administered. The results of students’ achievement in these two tests were used as the primary data of this research work. In analyzing the data, statistical analysis of paired sample t-test was used. The results of the analysis revealed that the average pre-test score reached by the students was 55.44, while in the post-test was 79.81. Besides, statistical computation indicated that t-cal t-table (t-count = 2.204 t-table = 2.026) in the significance level of 0.05 (5%). These findings confirmed that Beelinguapp was said to be effective in enhancing students’ reading comprehension of recount text. Thus, this research work rejected H0 and accepted Ha.